2016
DOI: 10.1136/oemed-2016-103678
|View full text |Cite
|
Sign up to set email alerts
|

CONSTANCES: a general prospective population-based cohort for occupational and environmental epidemiology: cohort profile

Abstract: Why the cohort was set up?CONSTANCES is a general-purpose cohort with a focus on occupational and environmental factors.Cohort participantsCONSTANCES was designed as a randomly selected sample of French adults aged 18–69 years at inception; 200 000 participants will be included.Data collection phasesAt enrolment, the participants are invited to complete questionnaires and to attend a health screening centre (HSC) for a health examination. A biobank will be set up. The follow-up includes an yearly self-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 34 publications
5
100
0
2
Order By: Relevance
“…We included participants of the French CONSTANCES cohort, a general-purpose population-based cohort intended to serve as an open epidemiological research infrastructure 42 , 43 . CONSTANCES was started in 2012 with the aim of collecting data from a total of 200,000 individuals over a 5-year period.…”
Section: Methodsmentioning
confidence: 99%
“…We included participants of the French CONSTANCES cohort, a general-purpose population-based cohort intended to serve as an open epidemiological research infrastructure 42 , 43 . CONSTANCES was started in 2012 with the aim of collecting data from a total of 200,000 individuals over a 5-year period.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure-disease associations obtained using physical exposures estimated from a JEM were similar to associations obtained from observations of individual workers (12). In a cross-national comparison of exposure estimates, we compared a French JEM based on self-reported physical exposures from a large cohort study (CONSTANCES -Cohorte des consultants des Centres d'examens de santé) (14,15) with the American O*NET JEM based on exposure information provided by expert job analysts and from surveys of workers in different jobs. We found that exposure estimates from these two general population JEM were strongly related, suggesting that results obtained from different general population JEM were likely to be comparable.…”
mentioning
confidence: 86%
“…CONSTANCES job exposure matrix. A general population physical exposure JEM was constructed from selfreported data obtained from CONSTANCES, a large cohort study of French salaried workers (14,15). Details of the creation of this JEM have been described in Evanoff et al (7).…”
Section: Individual-level Measuresmentioning
confidence: 99%
“…Im Vorfeld der Studie wurden thematische Arbeitsgruppen eingerichtet, die unter Sichtung der existierenden Literatur und in Abgleich mit anderen großen Kohortenstudien, wie etwa der britischen"UKBiobank" [7]und derfranzösischen Studie CONSTANCES [8], die Erhebungsmodule entwickelt haben. Diese wurden anschließend hinsichtlich Machbarkeit, Validität und Reliabilität in zahlreichen Pilotstudien überprüft [9], bevor sie in das finale Untersuchungsprogramm übernommen wurden.…”
Section: Krankheitsgruppen Und Deren Jeweilige Untersuchungsmoduleunclassified